Health from your pocket? Opportunities and limitations of health-related apps - Peter Enste; Sebastian Merkel; Sascha Romanowski (Institut Arbeit und Technik (IAT), 2010)
Nowadays more than half of all Germans (52.6%) inform themselves about health topics online. It is expected that in 2011 every third mobile phone sold will be a smartphone. At the moment there are more than 300,000 applications available since the introduction of the Apple online store in July 2008; by the end of September, they have been downloaded seven billion times. In Germany, about 1400 Health Apps are available, internationally there are already more than 7000. Health Apps play a minor role currently, but have, according to the online shop, growth rates of up to 156.6% (Android Market). Although many telemedicine solutions share the same or a similar value proposition they rely on different technical innovations. Smartphones / apps can serve as a uniform interface and thus decrease deficiencies in user acceptance and competence. Economically and from a consumer point of view, there lies a great potential in the development of health-related apps, which is (still) not fully utilized
urn:nbn:de:0176-201013024
Keywords: 330